Indigenous Tribute in Pre-Columbian and Christian Religious Mesoamerican Context - Ruiz Medrano, Ethelia (L'Uomo società tradizione sviluppo, 2024)
Several cases exist in which indigenous communities combine traditional ritual objects – especially codices – with Christian liturgical elements such as choir books, papal bulls, and sculptural images. This relationship demonstrates a dynamic and flexible indigenous ideology, in which Indigenous people aim to integrate and incorporate, rather than merge or blend, culturally foreign elements into their own. Here, we focus on one exceptional and almost unknown case. The convent of Tlaquiltenango (Morelos) was built in the second half of the Sixteenth century by Indigenous people working for Franciscan friars, and was later occupied by Dominican friars. In the cloister walls of this beautiful convent, more than one hundred fragments of Indigenous traditional pictography were hidden, discovered at the beginning of the Twentieth century. The fragments had been concealed by Indigenous people since the Sixteenth century using lime. The main subject of these fragments is tribute payment, similar to several other cases we have identified. In this paper, we aim to explore some ideas about why tribute payment frequently emerges as the primary theme in Indigenous objects hidden inside Christian objects. Our hypothesis is that tribute payment, prior to the conquest, carried important connotations that linked Indigenous commoners with their traditional lords and authorities, as well as with their gods. These connotations have not been sufficiently emphasized and their study may help us understand why some Indigenous people concealed tribute codices inside Christian objects during the Sixteenth century and possibly thereafter. Here we present an example of the concealment of Indigenous objects as a form of homage to their traditional rulers.